The particular kindness of friends: ex-Fascists, clientage and the transition to democracy in Italy, 1945–1960. Issue 4 (November 2015) - Evangelista, Rhiannon
Abstract : This article examines some of the social implications of Italy's limited purge of the bureaucracy and Fascist political class following the Second World War. Using the postwar personal correspondence of former Fascist government ministers Giuseppe Bottai (1895–1959) and Dino Alfieri (1886–1966), the article analyses the informal networks that promoted the continued influence of these ex-Fascists with high-ranking bureaucrats and other prominent individuals (such as Pope Paul VI and Aldo Moro). Thanks to the long-standing social practice of the raccomandazione, Bottai and Alfieri maintained their Fascist-era connections well into the postwar period, often serving as intermediaries between 'ordinary Italians' and governmental, political and cultural elites. Although they no longer held political power, these ex-Fascists represented a class of 'alternative elites' unassociated with the democratic values of the new Republic.